Partners in play: Exploring 'playing with' children living with severe physical and intellectual disabilities. (November 2021) - O'Connor, Deirdre; Butler, Alison; Lynch, Helen
Introduction: Play occupation is central to children's occupational lives and play is established as a fundamental right. While children with disabilities are at increased risk of play deprivation, few studies have explored the play occupation of children living with severe physical and intellectual disabilities. Method: Informed by an ethnographic approach, this qualitative study involved 17 participants including five families of children with severe disabilities and six classroom staff. Methods combined observations of children's play with adult interviews and focus groups to explore factors that influence play in home and school contexts. Findings were analysed using thematic analysis. Findings: Three themes emerged: (a) play as an occupation, play as an activity; (b) an empowered and empowering play partner; (c) the 'just-right' play object and environment. Conclusion: The influence of an empowering and empowered play partner combined with the suitability of the object and environment was central to successful play. A commitment to play for fun, for the wellbeing of these children, and by 'playing with' and not 'doing-to' the child was fundamental. Although the findings are specific to this study, play facilitators may use them to inform future play interactions through an enhanced understanding of empowerment and enablement for successful play occupation.